Grafting reactions of living macroanions with multi-walled carbon nanotubes - Baskaran, Durairaj; Sakellariou, Georgios; Mays, Jimmy W.; Bratcher, Matthew S. (Journal of Nanoscience and Nanotechnology, 2007)
Grafting reactions of living polystyryllithium (PSLi) with acid chloride containing multi-walled carbon nanotubes (MWNTs-COCl) were performed under vacuum in benzene at room temperature. Covalent grafting of polystyrene (PS) was characterized using spectroscopic, microscopic, and thermogravimetric analyses. Grafting at different ratios of macroanion to acylchloride of the carbon nanotubes showed that the grafting efficiency was not dependent on the concentration of the macroanions. The mole percent of PS present in the MWNTs-g-PS samples was inversely proportional to the precursor molecular weight of PSLi. Direct reactions of PSLi, polybutadienyllithium and n-butyllithium with pristine MWNTs without any functional groups were also performed in the presence and in the absence of tetrahydrofuran in benzene. The grafting reactions of living macroanions either with MWNTs-COCl or with pristine MWNTs indicated a partial grafting of polymer on the carbon nanotubes in benzene at room temperature.
Keywords: Anionic polymerization; covalent functionalization; grafting; multi-walled carbon nanotubes